''Carbon footprinting'': towards a universally accepted definition. Issue 1 (February 2011) - Wright, Laurence A; Kemp, Simon; Williams, Ian
As the threat of climate change becomes more acute, so does the need for adequate measures of impact(s), management and mitigation. Although carbon footprints are increasingly being used by organizations in the public and private sectors, a number of challenges and questions need to be addressed; among them, what does the term ''carbon footprint'' actually mean? The term needs a universally accepted definition before a consistent, accurate, comparable and transferable methodology can be developed. This article investigates the range of current definitions proposed for a carbon footprint in the context of inventoried emissions, applications, boundaries and limitations. We argue that to only account for CO2 emissions would result in the omission of almost a third of GHGs and a significant gap in their global management, whilst inclusion of all GHGs is very time-consuming and expensive, and should be considered only in system-specific life cycle-based assessments; this requires a separate definition, name and methodology. We suggest that as data collection for CO2 and CH4 emissions is relatively straightforward, these two carbon-based gases should be used in the determination of a carbon footprint. This should allow the carbon footprint to become a cost-effective, practical and repeatable metric that can be adopted by all types of organizations across the globe as a ''baseline'' indicator. However, it is likely that a more comprehensive metric will be required in some circumstances and by some organizations, so we also propose further GHG inclusion for full life cycle assessment-based assessments; where complete data is obtainable it can be used to provide a ''climate footprint''. This name reflects the addition of noncarbon-based gases and encompasses the full range of gases used in the global political community''s response in managing climate change. We conclude by considering lessons learnt with the proposal of sound and pragmatic definitions.